Blog Quality Assessment Tool (BQAT) - Muhammad Zain, Zuhaira; Abdul Ghani, Abdul Azim (Association of Technology and Science, 2015)
A blog quality model and guidelines to determine important features of different blog categories have been proposed to determine blog quality and to promote readers’ satisfaction. However, no tools have been developed to assist blog readers in the evaluation of their favorite blogs based on their blog satisfaction. This paper discusses each process in the development of the Blog Quality Assessment Tool (BQAT) in detail. The main functions of the BQAT are to calculate the probability of a blog to be of good quality based on blog-reader satisfaction, and to accumulate the results for the assessed blog. Thus, blog-readers can easily assess their favourite blogs and obtain information on the quality of the blogs visited. This study also shows that the more satisfied the blog is, the higher its quality.